قياس تفاوت مستوى التنمية البشريه في المحافظات العراقيه لعام 2007 باستخدام طريقة المركبات الرئيسيه - رسول نجاح (University of Thi-Qar Journal of Science, 2008)
This statistical research contains the measuring the variation of human development level in Iraq in 1997 by using an important statistical method and the data of the statistical survey in 1997 , in the order to get knowledge about the effect of some factory on the human development like (water , level of education ,………, etc) more than other factors in the Iraqi governorates (except Kurdistan) we find these factors are very effective on the human development level especially in AL-Mothanna governorate which has the lowest development level and then mesan, AL-Kadessiyah , Thi-Qar and Waset . Lorenz curve and Geni coefficient are also gave us this result .